A vocabulary of images : child art in Australia and the advocacy of Marianne Seemann. (Common Ground, 2020)
"This book grew out of an interest in the Children's Craft and Leisure movement that started in Australia in 1922. The idea of children as naturally creative and the necessity to protect them from formal art education lest they lose their unspoiled perception of truth and beauty was a strong belief at the time. It was also a time where children of the poor and the working classes were starting to be included in artistic endeavours as there was a perception that as work practices changed there would be leisure time for all that could be gainfully employed if early education prepared children to grow their creative imagination. 100 years later the belief in children's innate creativity is still strong in the early childhood education canon. In this volume, we trace the attraction Child Art had in Australia. Marianne Seemann is the exemplar we take to follow the rise and fall of the movement as she was an embodiment of the most important years. She came from Vienna, had worked closely with the creator of Child Art, was a disciple of Franz Cizek (the Father of Child Art), and never deviated from his teachings. The story told in this book started in Vienna. Marianne Seemann (formerly Mendl), 1897-1967, grew up in a wealthy, artistic Jewish family in Vienna. Interested in dance and painting she worked with the likes of Grete Wiesenthall but it was her interest in Child Art that would become her life's work. Marianne studied at Franz Cizek's Juvenile Art Class in Vienna and then became an enthusiastic assistant in his classes. She would maintain contact with him until his death in 1946 although by that time they were at opposite ends of the world. Through the Juvenile Art Class, Marianne found she was well connected with progressive educationalists when she arrived in Australia. Many of the ideas welcomed by the progressive educationalists were exciting beliefs about the ideal of education and concepts of progress. Revisiting these ideas in a form that brings into focus the practices of those who supported the 'new education' is an opportunity to evaluate what legacies have not been acknowledged and what ideals have lost relevance for the present"--